Implikasi PTM terbatas terhadap Perkembangan Ranah Afektif dan Ranah Psikomotorik Peserta Didik pada Mata Pelajaran PAI di UPT SMA Negeri 1 Palopo - Damsi, Khairawati (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2022)
Focusing on the form of implementing PTM is limited to PAI subjects. The purpose of this study, the implications of PTM are limited to the affective and psychomotor domains of students in PAI subjects at UPT SMA Negeri 1 Palopo. This type of descriptive qualitative research. The results of the study show that the implementation of limited PTM is highly appreciated by teachers and students because the learning interactions are different when online so that students experience the direct transfer of knowledge, attitudes, and different learning experiences. Implementation of limited face-to-face learning is carried out in accordance with health protocol procedures, guidelines for implementing limited PTM during the New Normal period. The school has planned and carried out in accordance with limited face-to-face learning procedures, but in terms of implementing the teaching and learning process in class, the delivery of material is quite condensed, and only conveys important points and emphasizes the completion of assignments, so that students are driven by time and maximize time. available so that they must focus on following the lesson. Teachers do not use interactive learning models and do not involve innovative learning media that support the concrete delivery of information to students, so that this has implications for the development of the affective and psychomotor domains of students as well as student activities in schools and the development of these two aspects cannot be carried out maximally.